2023
DOI: 10.1109/access.2022.3233197
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Challenges to Circular Economy in Indian Fashion Industry

Abstract: The fashion industry, during production and post-consumption, has major adverse environmental impacts. With the recent circular economy (CE) practices initiative, discarded fashion materials are reused to recover value from the waste. However, the CE practices initiative have not been well-received by society. The role of CE practices is very crucial in fashion industry as it helps in lowering the environmental burden caused by the discarded fashion materials, which in turn help to achieve the sustainable deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 76 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Nevertheless, the effectiveness and comparability of the existing Corporate Social Responsibility (CSR) reporting in representing the real objectives and actions of clothing businesses are lacking (Kozlowski, 2012). As part of its shift to a purposedriven approach, the sector is highlighting the circular economy (CE) as a crucial sustainability paradigm (Harsono et al, 2024;Thinakaran et al, 2022). In an effort to meet consumer demand and lessen the industry's substantial environmental effectssuch as carbon emissions, textile waste, and resource depletion-businesses are putting a greater emphasis on sustainability.…”
Section: Corporate Social Responsibility (Csr) In Fashionmentioning
confidence: 99%
“…Nevertheless, the effectiveness and comparability of the existing Corporate Social Responsibility (CSR) reporting in representing the real objectives and actions of clothing businesses are lacking (Kozlowski, 2012). As part of its shift to a purposedriven approach, the sector is highlighting the circular economy (CE) as a crucial sustainability paradigm (Harsono et al, 2024;Thinakaran et al, 2022). In an effort to meet consumer demand and lessen the industry's substantial environmental effectssuch as carbon emissions, textile waste, and resource depletion-businesses are putting a greater emphasis on sustainability.…”
Section: Corporate Social Responsibility (Csr) In Fashionmentioning
confidence: 99%
“…Step 3: NIRDM of factors was calculated by Equation (2). Fuzzy NIRDM of key barriers to recycling in the textile industry is obtained.…”
Section: Five-point Scalementioning
confidence: 99%
“…Thus, the manufacturing community is in a situation to adopt CE practices to ensure sustainable industrial practice [1]. The need to adopt CE practices has been more compelling for the textile industry as it is the second most polluting industrial sector in the world [2]. The toxic substances released during the processing activities of the textile industry pollute the air, water, and soil heavily.…”
Section: Introductionmentioning
confidence: 99%
“…Annually, almost $400 billion of clothing is wasted, with an anticipated increase of 60% between 2015 and 2024. In contrast, the recycling or reuse of textile material waste is limited to 25%, with the remaining 75% deposited in landfills (Thinakaran et al, 2023). Consequently, concerns regarding sustainable development stem from unsustainable textile production and consumption patterns.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Saha et al (2022) uncovered the current state of the circular economy (CE) in the textile and apparel sector based on a sample dataset of 114 textile firms from Bangladesh, Vietnam, and India. Thinakaran et al (2023) identified the challenges of implementing CE in Indian fashion industry. Camacho-Otero et al (2019) studied consumer perspectives on accepting and adopting circular offerings.…”
Section: Introductionmentioning
confidence: 99%